2=-2(y+3)

Simple and best practice solution for 2=-2(y+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2=-2(y+3) equation:


Simplifying
2 = -2(y + 3)

Reorder the terms:
2 = -2(3 + y)
2 = (3 * -2 + y * -2)
2 = (-6 + -2y)

Solving
2 = -6 + -2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '2y' to each side of the equation.
2 + 2y = -6 + -2y + 2y

Combine like terms: -2y + 2y = 0
2 + 2y = -6 + 0
2 + 2y = -6

Add '-2' to each side of the equation.
2 + -2 + 2y = -6 + -2

Combine like terms: 2 + -2 = 0
0 + 2y = -6 + -2
2y = -6 + -2

Combine like terms: -6 + -2 = -8
2y = -8

Divide each side by '2'.
y = -4

Simplifying
y = -4

See similar equations:

| 15x+15y-2xy=0 | | 50+2x= | | -5(2x-19)=2(x-8)-9 | | 2(c+2)+6=5(x-5) | | 125x+1382=284 | | 3(z-4)-1=4(z-5) | | x*ln(x)-2=0 | | 2x^2+30x+99=0 | | y^2-2y-104=0 | | 4x^2-23x-35=o | | 12x+13=21 | | 8(x-2)=-6(x+4)+43 | | u+7=-6 | | (-5a^6-7)-(-14a^6)= | | x=100+-3x | | Y^3-7y^2=8 | | 32+4x=4(-x+7)-44 | | -2+v=3 | | 9x-88=2x-11 | | Y/3-12=8 | | 4[3+2(x+5)]=76 | | 29+8(q-11)=-12 | | 5x-1(-7x+9)=15 | | (4w^2-15)-(-15w^2)= | | 0.75m-0.5=2+0.25m | | 0.71m-0.5=2+0.25m | | 3x-54=-2 | | 6x+3y=190 | | f(x)=-2senx | | 18x-(4x-2)=142 | | 4d=-8+3d | | D-9.8=-3.2 |

Equations solver categories